Towards useful and usable interaction design tools: CanonSketch - Campos, Pedro (2021)
Despite all the effort dedicated to bringing better User-Centered Design (UCD) tools to market, current studies show that the industry is still dominated by tools that do not support the activities and workstyles of designers. Also, there is a growing need for interaction design tools aimed at software engineers, a problem related to bringing usability into the software engineering processes. We propose a new workstyle model that can be effectively used to envision, design and evaluate a new generation of innovative interaction and software design tools, aimed at integrating usability and software engineering. We illustrate the effectiveness of our model by describing a new tool, called CanonSketch, that was built in order to support UCD in terms of the dimensions in our workstyle model. We also describe an evaluation study aimed at contrasting paper prototyping with our tool as well as the level of workstyle support.